Breaking the Curse of Sisyphus : An Empirical Analysis of Post-Conflict Economic Transitions - Cevik, Serhan (IMF Working Papers; Working Paper ;, 2013)
This paper provides a broad empirical analysis of the determinants of post-conflict economic transitions across the world during the period 1960-2010, using a dynamic panel estimation approach based on the system-generalized method of moments. In addition to an array of demographic, economic, geographic, and institutional variables, we introduce an estimated risk of conflict recurrence as an explanatory variable in the growth regression, because post-conflict countries have a tendency to relapse into subsequent conflicts even years after the cessation of violence. The empirical results show that domestic factors, including the estimated probability of conflict recurrence, as well as a range of external variables, contribute to post-conflict economic performance.